Representações do feminino decolonial na obra de Chimamanda Ngozi Adichie - Pereira, Maiara Cristina Segato Rocha (2025)
Chimamanda Ngozi Adichie is currently one of africa's best-known and read authors. The choice for this author seemed important to us, not only because she belongs to the new generation of well-known writers, but also because, in her approach to African society, we can find traces of feminist critical thinking when dealing with unequal relations between men and women, also marked by conflicts inherent in Nigerian culture, caused by the colonization process that occurred in the country. In this sense, his works present the attempt to understand how the identities(s) of the postcolonial subject, especially the feminine, are constructed and established after colonialism and how imperialism can interfere in the construction and affirmation of cultural identity. In this study, we propose to think to what extent the relations of coloniality influenced the spaces of constitution/social insertion of female postcolonial subjects and the formation of their identities and how these processes are fictionalized in the literature. The present research has as object of study the work of the Nigerian writer Chimamanda Ngozi Adichie, inserted in the postcolonial scenario, with emphasis on the romance Purple Hibiscus [2003], (2011). This work composes the main corpus of study, however, whenever the analytical exercise is important to extend the dialogue, we will place in comparison other works of the author. To carry out this study, we will use theoretical conceptions related to the insertion of subjects in post-colonialism, gender relations between men and women in African society and the identity formations of black individuals in the postcolonial context. We believe that postcolonial studies, at their intersection with feminism, especially decolonial feminism, can value the literary historiography of countries that have experienced the process of colonization. These issues appear in the construction of characters and in the construction of the space/time of the narration in the works of the Nigerian writer. We believe that the study of Adichie's work, as proposed here, can shed light on african literature by female authorship and the relationship of coloniality/decoloniality of power.